2013
DOI: 10.1101/001552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancient human genomes suggest three ancestral populations for present-day Europeans

Abstract: We sequenced genomes from a ~7,000 year old early farmer from Stuttgart in Germany, an ~8,000 year old hunter-gatherer from Luxembourg, and seven ~8,000 year old hunter-gatherers from southern Sweden. We analyzed these data together with other ancient genomes and 2,345 contemporary humans to show that the great majority of present-day Europeans derive from at least three highly differentiated populations: West European Hunter-Gatherers (WHG), who contributed ancestry to all Europeans but not to Near Easterners… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
754
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 371 publications
(788 citation statements)
references
References 87 publications
28
754
0
6
Order By: Relevance
“…Recent studies using ancient genomic data of Central and North European early farmers have shown an affinity to South European rather than Near Eastern populations [33,40,41]. Of note, the proportion of western hunter-gatherer ancestry is higher in all modern-day Europeans and the early farmer ancestry being comparably best preserved in, for example, Sardinians [33,40].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies using ancient genomic data of Central and North European early farmers have shown an affinity to South European rather than Near Eastern populations [33,40,41]. Of note, the proportion of western hunter-gatherer ancestry is higher in all modern-day Europeans and the early farmer ancestry being comparably best preserved in, for example, Sardinians [33,40].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-haplogroup U5b has been shown to be common in hunter-gatherer communities across Europe [28][29][30]32,33,47,48]. Contrary to the low mtDNA diversity observed in Central/North European hunter-gatherers [28][29][30], we identify a higher variability in early farming communities of the Carpathian Basin including haplogroups N1a, T1, T2, J, K, H, HV, V, W, X, U2, U3, U4 and U5a (electronic supplementary material, table S1).…”
Section: Results (A) Mitochondrial Dnamentioning
confidence: 99%
See 3 more Smart Citations